Brodalumab for the treatment of psoriasis. (1st December 2016) - Galluzzo, M.; D'adamio, S.; Bianchi, L.; Talamonti, M.
ABSTRACT: Introduction : Psoriasis is a complex disease in which the alteration of the IL-23/Th17 axis appears to be crucial for its pathogenic mechanisms, and anti-IL17 agents are rapidly becoming important therapeutic tools. Brodalumab, a fully human Chinese hamster ovary cell-derived immunoglobulin G2 (IgG2) anti-IL-17RA monoclonal antibody, is currently the most-developed treatment that binds to the IL-17RA. The authors review and provide updates of efficacy and safety by several studies on brodalumab. Areas covered : A PubMed search was performed for relevant literature. Among the trials of brodalumab, the most common adverse events included nasopharyngitis, headache, upper respiratory tract infection, and arthralgia. Suicidal ideation and completed suicides had been observed in the brodalumab programme, although evidence to date was quoted as not suggesting a causal association. Expert commentary : By blocking the IL-17 receptor A, brodalumab antagonizes signaling from IL-17A, IL-17F, IL-17A/F and IL-25, and this probably contributes to the high efficacy observed in clinical trials. Considering the different therapeutic target and the potential biological implications that blocking IL-17RA instead of IL-17A might have, brodalumab may not necessarily belong to the same class that includes secukinumab and ixekizumab, but it may be classified in a distinct group.